Socio-environmental impacts of mineral mining and conflicts in Southern and West Africa: navigating reflexive governance for environmental justice - Llewellyn Leonard (Environmental Research Letters, 2024)
Mineral mining activities in Africa have long been associated with a myriad of socio-environmental impacts and conflicts, posing significant challenges to sustainable development and environmental justice. This paper explores the complex interplay between mineral mining, socio-environmental impacts, and conflicts in the Southern and West African region, with a focus on the imperative of reflexive governance for achieving just transitions and environmental justice. Drawing on a comprehensive literature review and cases from Southern and Western African countries, this paper examines the multifaceted nature of socio-environmental impacts resulting from mineral mining. These impacts encompass ecological degradation and social inequalities, among others. Furthermore, the paper delves into the dynamics of conflicts arising from mineral mining and competing interests such as natural resources and land rights. Additionally, the paper examines governance structures aimed at enhancing transparency, accountability, and environmental sustainability. The paper concludes by highlighting the implications of reflexive governance as a transformative tool for addressing the socio-environmental impacts of mineral mining and conflicts in Southern and West Africa. It underscores the urgency of adopting holistic and integrated approaches that prioritize environmental protection, social equity, and community well-being in the context of mineral resource extraction. The African Union can serve as the catalyst for reflexive governance and environmental justice in mineral resource extraction, with citizens also holding national governments accountable.